PERMASALAHAN DAN UPAYA PENYELESAIAN SENGKETA KONTRAK PENGADAAN BARANG/JASA PEMERINTAH - Herry Anto Simanjuntak (JURNAL JUSTIQA, 2022)
In general, in making an agreement/agreement it is always preceded by an agreement and then it is stated in a letter or deed in this case when it comes to government goods/services it must be carried out in an agreement called a contract. The contract will state the rights and obligations of the parties who are the reference in carrying out a job with the aim that the parties bound in the contract are able to comply and submit in accordance with the contents of the contract agreement made. It is undeniable and frequent dissatisfaction by the Commitment Making Officer (PPK) for the implementation of the contract by the provider of goods/services. Such dissatisfaction can lead to unilateral termination of the contract by the Committing Officer, which is followed by other actions such as collecting a full refund of the advance and blacklisting the provider of goods/services. Meanwhile, the provider of goods/services will not simply accept the act of terminating the contract by the PPK. The provider of goods/services will try to submit various reasons and defenses. Thus, the termination of the contract can cause a dispute between the PPK and the provider of goods/services. To accommodate problems that often arise in the field, Law Number 30 of 1999 concerning Arbitration and Alternative General Dispute Resolution has regulated procedures for resolving disputes between contracting parties. In addition, specifically for government goods/services procurement contracts, provisions regarding contract termination are also found in Presidential Regulation number 54 of 2010. Contract dispute resolution is not only resolved according to the law but in practice in the field, dispute resolution can be carried out by means of deliberation between the disputing parties. , and if there is a stalemate, the final settlement is carried out through legal channels in court.